ENTREPRENEURIAL KNOWLEDGE, ENTREPRENEURIAL CHARACTERISTICS TO THE SUCCESS OF SMALL AND MEDIUM ENTERPRISESGUITAR INDUSTRY CENTER IN KEMBANGAN VILLAGE, BAKI, SUKOHARJO - Sakidi Sakidi; Istiatin Istiatin; Legowo Dwi Resihono; Ari Susanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research is used to determine the magnitude of influence and significance between entrepreneurial knowledge variables and entrepreneurial characteristics to the success of small and medium enterprisesin the guitar industry center in Kembangan Village, Baki, Sukoharjo. The population in this study was obtained from village data of 80 guitar speakers in Kembangan Village, Baki District, Sukoharjo Regency. Because the population is less than 100 respondents, the sample used is the entire population of 80 who responded as a Guitar Industry Center Business Actor in Kembangan Village, Baki, Sukoharjo. The technique in this study uses non-probability sampling with saturated sampling types. The data analysis technique in this study is a multiple linear regression using SPSS software. Before analyzing data with multiple linear regression, instrument tests and classical assumption tests have been conducted first in concluding this research data so as not to be biased so that research is feasible. From the research results, it is known that entrepreneurial knowledge and characteristics have a positive and significant influence. The Result of Anaisis Coefficient of Determination (R2) obtained a result of 0.674 or 67.4%. This means that the ability of independent variables (entrepreneurial knowledge, characteristics) in this study affected dependent variables by 67.4%. The remaining 32.6% is explained by other variables not included in the regression model. Keyword :